S75 Asthma exacerbations in routine clinical practice during COVID-19 in England in 2020. (11th November 2022) - Rothnie, KJ; Tritton, T; Han, X; Holbrook, T; Numbere, B; Ford, AF; Massey, L; Fu, Q; Hutchinson, FM; Birch, HJ; Leather, D; Sharma, R; et al.
Abstract : Introduction/Objectives: The COVID-19 pandemic is recent and ongoing and there is limited evidence of the impact of COVID-19 on the burden associated with patients with respiratory diseases. This study evaluated the impact of the COVID-19 in the early part of the pandemic on this patient population. The study objective was to describe changes over time in asthma exacerbation frequency stratified by disease severity. Methods: This was a retrospective dynamic cohort study of English asthma patients aged ≥18 years, for the period from Mar 2018 until Aug 2020 using the Clinical Practice Research Datalink Aurum linked to Hospital Episode Statistics datasets. The proportion of patients experiencing a severe asthma exacerbation, which was defined as a hospital admission for an exacerbation, was described monthly stratified by 2019 GINA treatment step at baseline. Results: In total, 823, 645 incident and prevalent asthma patients (mean [SD] age: 51.4 [17.7] years, 58.1% females) were included; 21.3%, 3.9%, 23.6%, 12.7%, 3.1% and 35.4% of patients were in GINA step 1/2, GINA step 2, GINA step 3, GINA step 4, GINA step 5 treatment step and the unclassifiable group respectively, at index. The proportion of patients to experience a severe exacerbation over time, stratified by GINA treatment step at baseline, is shown in figure 1 . The proportion of patients to experience a severe exacerbation in each GINA step subgroup showed seasonal peaks in January 2019 and December 2019, and a peak in March 2020 before declining steeply to May 2020 and remaining low until August 2020. Conclusion: Among patients with asthma, the frequency of severe exacerbations declined steeply between March 2020 and May 2020 for all stratification groups and remained low through to August 2020. When comparing GINA step at baseline, a higher proportion of patients in GINA steps 4 and step 5 experienced a severe exacerbation compared with patients in GINA steps 1/2, step 2 and step 3 throughout the observation period. Further research on the long-term impact of COVID-19 on asthma exacerbations in routine clinical practice in England is warranted. Please refer to page A211 for declarations of interest related to this abstract.